Comparative advantage of livestock component in reduction of poverty – logistic regression approach - G. Senthilkumar; K. N. Selvakumar; M. Prabu; A. Serma Saravana Pandian; C. Valli; B. Jayavarathan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A logistic model was fitted for the sample respondents to explore the determinant factors of poverty and comparative advantage of livestock component in reduction of poverty was ascertained. The primary data were collected through personal interview from randomly selected 540 sample households from six poverty prone districts using pre-tested interview schedules. Among various variables presumed to be the determinants of poverty, the variables viz., Ariyalur district dummy, cattle holding, sheep holding, family size, family dependency ratio were found to be statistically significant and rest were non-significant. The number of cattle and sheep were found to reduce the probability of fell down below the poverty line. Thus, these components may be considered while framing any poverty alleviation programmes in rural India.